2021
DOI: 10.15430/jcp.2021.26.4.298
|View full text |Cite
|
Sign up to set email alerts
|

Primary Care Provider Knowledge and Practice in Risk Assessment for Early Age Onset Colorectal Cancer: Opportunities for Improvement

Abstract: The incidence and mortality of colorectal cancer (CRC) in patients under the age of 50, or early age onset (EAO) CRC, are rising; 11% of all colon cancers and 15% of all rectal cancers in the United States (US) are diagnosed in individuals under age 50 [1-3]. EAO-CRC patients commonly present with symptoms, such as hematochezia and iron deficiency anemia (IDA) [4,5]; thus professional societies currently recommend lower endoscopic evaluation for patients with unexplained symptoms [6,7]. Unfortunately, there is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Inadequate inquiries about family history of CRC or advanced adenomas and age of cancer onset likely contributes to untimely screening for increased-risk individuals. One study reported only 70% of primary care physicians routinely recommended CRC screening in young adults (40-to-49 years of age) with a first degree relative with colorectal cancer ( 26 ). Future studies assessing the barriers limiting inquiries (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Inadequate inquiries about family history of CRC or advanced adenomas and age of cancer onset likely contributes to untimely screening for increased-risk individuals. One study reported only 70% of primary care physicians routinely recommended CRC screening in young adults (40-to-49 years of age) with a first degree relative with colorectal cancer ( 26 ). Future studies assessing the barriers limiting inquiries (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Globally, colorectal cancer (CRC) among individuals under the age of 50 is commonly referred to as early-onset colorectal cancer (EOCRC), 1 and its incidence is steadily increasing, 2,3 with China being no exception. 4 EOCRC tends to be more subtle, typically being diagnosed in later stages and having a poorer prognosis, [5][6][7] leading to greater disability and higher healthcare expenses.…”
Section: Introductionmentioning
confidence: 99%
“…Possible explanations include patient-related factors, such as lack of knowledge about symptoms which may contribute to a longer time to diagnosis [12,13]. Provider-related factors have also been shown to play a role in delaying diagnosis where, despite younger patients presenting with symptoms that should prompt investigation of CRC, there may be a low suspicion among health care providers [14,15]. Given these issues, our objectives were to (1) characterize the pattern of symptoms at presentation in EoCRC compared to LoCRC, (2) identify differences in the number of symptoms at presentation and whether this associates with survival, and (3) assess if EoCRC patients experience a longer time to diagnosis compared to LoCRC and how this impacts survival.…”
Section: Introductionmentioning
confidence: 99%